Exploring and supporting older women's chemotherapy decision-making in early-stage breast cancer. Issue 2 (March 2022) - Karuturi, Meghan S.; Giordano, Sharon H.; Hoover, Diana S.; Volk, Robert J.; Housten, Ashley J.
Abstract: Background: Few studies have focused on the therapeutic decision-making process in older adults with breast cancer. This study investigated older adult breast cancer patients' perspectives on neo/adjuvant chemotherapy, thereby identifying informational needs and preferences as patients navigate the treatment decision-making process. Materials and methods: Women ≥65 years diagnosed with early-stage breast cancer were recruited from an academic cancer center after deciding whether or not to receive neo/adjuvant chemotherapy. Participants completed surveys assessing sociodemographic characteristics, health literacy/numeracy, and shared decision making. They took part in individual semi-structured interviews to explore their perspectives, experiences, and values regarding treatment. Interviews were audio-recorded and transcribed. Transcripts were analyzed using the Sort and Sift, Think and Shift qualitative approach. Quantitative data was summarized using descriptive statistics. Results: Of the 26 participants (age range 65–92 years; 81% non-Hispanic White; 72% ≥ college degree; 50% unmarried), 58% elected to undergo chemotherapy and 42% declined. The majority of participants had adequate health literacy/numeracy and engaged in shared decision-making. Thematic analysis revealed several commonalities regardless of the decision to undergo chemotherapy. Participants sought information regarding their disease/treatment. They referenced subjective experiences of friends/family members with cancer. Self-perception of health and the side effects of chemotherapy were also key factors. Participants placed importance on the maintenance of quality of life throughout treatment. Conclusions: Decision-making strategies in older patients were shaped by knowledge, values, and the anecdotal experiences of others. Results can inform the development of decision support tools for older patients and physicians to better facilitate the shared decision-making process.